استراتيجية تعليم الفكر والتكلم والكتابة (Think Talk Write) لترقية مهارة الكتابة - Sholehan; Muflihah; Sa’adah, Zumrotus; Maghfiroh, Lailatul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
One way to encourage and improve writing skills is to think, talk, and write. In this study, researchers used one of the learning strategies that are expected to improve students' writing skills (Maharah Kitabah). The learning strategy is Think Talk Write (TTW). The purpose of this research is to find out the basic concept of Think Talk Write (TTW) and how it is applied in learning Arabic, especially in writing skills. The research method used by the researcher is a field study method. The researcher used qualitative methods to obtain data on the relationship between thinking, speaking, and writing learning strategies on writing skills and improving writing skills or Maharah Kitabah. The Think Talk Write (TTW) strategy can be one of the media for evaluating schools about the importance of teaching Arabic with Think strategies. Talk Write to improve linguistic competence in understanding writing in studying it. In addition, TTW can also improve students' writing skills in learning Arabic and be interesting and not bored during teaching. Think Talk Write strategy is learning that begins with thinking while reading (listeners, given input for learning), and the speaker's learning outcomes with presentations and discussions and make reports. The result is a presentation. This strategy allows students to communicate in discussions so that they can improve their writing skills and help students communicate their ideas and understand the subject matter.